Knowledge, skills and competences for recovery and growth : work programme 2010 - (:unkn) unknown (Publications Office of the European Union, 2010)
"This work programme outlines how Cedefop will support European VET policy in 2010. It is divided into: (a) a narrative reviewing the policy background and outlining how Cedefop will take forward its four priorities in 2010; (b) detailed activity and project fiches. They show the expected outcomes of Cedefop's activities and the outputs of each activity's projects that will help achieve them. The outcome indicators to measure performance for the activity are also shown in the fiches; (c) an activity-based budget (ABB) that shows the human and financial resources allocated to each activity." (Herausgeber, BIBB-Doku)
Keywords: S 3.5.5.1 CEDEFOP; S 2.3 Berufsbildungspolitik; I 2.2 Europa; CEDEFOP; Programm; Berufsbildung; Förderung; Internationale Zusammenarbeit; Berufsbildungspolitik; Europäische Union; 2010